2020
DOI: 10.5194/acp-20-2161-2020
|View full text |Cite
|
Sign up to set email alerts
|

Mutual promotion between aerosol particle liquid water and particulate nitrate enhancement leads to severe nitrate-dominated particulate matter pollution and low visibility

Abstract: Abstract. As has been the case in North America and western Europe, the SO2 emissions have substantially reduced in the North China Plain (NCP) in recent years. Differential rates of reduction in SO2 and NOx concentrations result in the frequent occurrence of particulate matter pollution dominated by nitrate (pNO3-) over the NCP. In this study, we observed a polluted episode with the particulate nitrate mass fraction in nonrefractory PM1 (NR-PM1) being up to 44 % during wintertime in Beijing. Based on this typ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 82 publications
(98 reference statements)
3
70
0
Order By: Relevance
“…LT) measurement data from October 2018 to February 2019 were selected for further analysis. As shown by Figure 3 and consistent with other observations in Beijing (Tang et al, 2016;Wang et al, 2020c), there was a general tendency for the PM2.5 mass concentration to increase with a decreasing MLH. Organic compounds and nitrate were the most abundant fractions of the daytime aerosol mass composition, contributing together approximately 70% to total NR-PM2.5 mass concentration.…”
Section: Connection Between the Aerosol Chemical Composition Light Esupporting
confidence: 91%
“…LT) measurement data from October 2018 to February 2019 were selected for further analysis. As shown by Figure 3 and consistent with other observations in Beijing (Tang et al, 2016;Wang et al, 2020c), there was a general tendency for the PM2.5 mass concentration to increase with a decreasing MLH. Organic compounds and nitrate were the most abundant fractions of the daytime aerosol mass composition, contributing together approximately 70% to total NR-PM2.5 mass concentration.…”
Section: Connection Between the Aerosol Chemical Composition Light Esupporting
confidence: 91%
“…In addition, a few studies investigated aerosol hygroscopic growth and CCN activities concurrently, and both consistencies (Wu et al, 2017;Zhang et al, 2017; and discrepancies (Ma et al, 2016; were reported. The discrepancies could be caused by several factors (Petters and Kreidenweis, 2008;Wex et al, 2009;Petters and Kreidenweis, 2013;, such as solution non-ideality of aerosol droplets, limited solubility of some components contained by aerosol particles, surface tension effects, liquid-liquid phase separation, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of emission sources has been widely recognized as the decisive factor of PM 2.5 pollution over urban agglomerations, including industrial exhaust, urban transportation, residential emission, power plants, agricultural activities, and bio-combustion (Huang et al, 2014;Tian et al, 2016;Wu et al, 2018;An et al, 2019). The outbreak, persistence, and dissipation of particle pollution generally depends on meteorological conditions and regional synoptic patterns controlled by the large-scale or synoptic-scale atmospheric circulation (Chuang et al, 2008;Zhang et al, 2012;Russo et al, 2014;Zheng et al, 2015;Shu et al, 2017;Li et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…port hub with sub-basin topography, central China is a region of transmission pollution characteristics affected by two reported transport pathways from the vast flatland in central eastern China (Yu et al, 2020) and from the NCP region (H. . In combination with high anthropogenic emissions (Wu et al, 2018) and secondary aerosol formation (Huang et al, 2020), central China often suffers severe pollution episodes in winter caused by PM 2.5 (Gong et al, 2015;Xu et al, 2017). In this study, we conduct a circulation classification to differentiate the synoptic modes during the severe particle pollution episodes in winter over central China from 2013 to 2018 by using the Lamb-Jenkinson method.…”
Section: Introductionmentioning
confidence: 99%